Strengthening Agricultural Regeneration: Determinants of Young Farmers’ Performance in Sub-Urban Villages - Sudrajat, Jajat; Fitrianti, Wanti; Suyatno, Adi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2025)
Farmer regeneration in Indonesia is faced with severe challenges, and it is predicted that this may lead to a decrease in the national food production ability. Therefore, strategic effort is required to facilitate the regeneration process. In this study, we aimed to analyze the dynamics of farmer regeneration in sub-urban villages and the determinants of the farming performance of a young farmer. The research method employed a mixed approach between qualitative and quantitative perspectives. In the quantitative method, we purposively selected 51 young farmers as samples for interview. The qualitative approach was used to explain the dynamics of regeneration behavior, whereas the quantitative approach based on Spearman correlation was used to analyze a few critical variables, which exhibited a strong correlation with a young farmer farming performance. The research results revealed a dynamic behavior of a farmer child, determining their entry into or exit from agriculture, and that farming income was the main determinant of decision-making in entering the agriculture sector. The analysis further revealed that a young farmer farming performance correlated significantly with their agricultural entrepreneurship orientation, which covers the feeling of confidence, patience, and perseverance in farming. Further, their farming performance was also correlated significantly with access to external finance  and agricultural education in the family. These results provide valuable insights regarding the importance of the empowerment strategy, particularly at farmer household level, in encouraging effective farmer regeneration.